2020
DOI: 10.1038/s41598-020-67599-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Kyasanur forest disease viremia, antibody kinetics, and virus infection in target organs of Macaca radiata

Abstract: The present manuscript deals with experimental infections of bonnet macaques ( Macaca radiata ) to study disease progression for better insights into the Kyasanur Forest Disease (KFD) pathogenesis and transmission. Experimentally, 10 monkeys were inoculated with KFD virus (KFDV) (high or low dose) and were regularly monitored and sampled for various body fluids and tissues at preset time points. We found that only 2 out of the 10 animals showed marked clinical signs becoming moribund, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
(56 reference statements)
2
14
0
Order By: Relevance
“…All the animals were clinically evaluated for skin/systemic disorders, haemoglobin, total leukocyte count, differential leukocyte count, platelet count, packed cell volume, biochemical parameters (AST, ALT, bilirubin, serum proteins, alkaline phosphatase, LDH, BUN, creatinine, cholesterol, triglycerides, sodium, potassium and glucose), abdominal ultrasonography, chest X-ray and tuberculin test and were found fit for the study. Animals were screened for Kyasanur forest disease virus and SARS-CoV-2 and IgG antibodies were found to be negative 29,30 . Biomedic data systems temperature transponder was implanted in the interscapular region subcutaneously for monitoring of body temperature during the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the animals were clinically evaluated for skin/systemic disorders, haemoglobin, total leukocyte count, differential leukocyte count, platelet count, packed cell volume, biochemical parameters (AST, ALT, bilirubin, serum proteins, alkaline phosphatase, LDH, BUN, creatinine, cholesterol, triglycerides, sodium, potassium and glucose), abdominal ultrasonography, chest X-ray and tuberculin test and were found fit for the study. Animals were screened for Kyasanur forest disease virus and SARS-CoV-2 and IgG antibodies were found to be negative 29,30 . Biomedic data systems temperature transponder was implanted in the interscapular region subcutaneously for monitoring of body temperature during the study.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-SARS-CoV-2 immunoreactivity in the lung tissues was assessed using mouse polyclonal serum. For IHC, mouse polyclonal serum was used as the primary antibody (1:500) and anti-mouse HRP antibody was used as secondary antibody 29,36 .…”
Section: Methodsmentioning
confidence: 99%
“…The acute phase is characterized by dehydration, hypotension, bradycardia and diarrhea, while neurological signs such as tremors may be observed in the second phase (17,18,20,21). However, platelets were only mildly decreased over infection, and no hemorrhagic signs were reported in these animals (18,19).…”
Section: Introductionmentioning
confidence: 80%
“…Experimental infection of these two NHP species demonstrated that blackfaced langurs in particular are highly susceptible to KFDV and succumbed to infection during the viremic phase (17). Bonnet macaques infected with KFDV experience a biphasic illness with 10-100% lethality depending on the study (17)(18)(19)(20). The acute phase is characterized by dehydration, hypotension, bradycardia and diarrhea, while neurological signs such as tremors may be observed in the second phase (17,18,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Gross examination of lungs was done to assess the degree and extent of consolidation and congestion as per the recommendation of the Working Group of the Society of Toxicologic Pathology’s Scientific and Regulatory Policy Committee (38). Histopathological examination of various lung lobes was carried out to assess the extent of interstial pneumonia, alveolar damage, haemorrhages, inflammatory cell infiltration, hyaline membrane formation and accumulation of eosinophilic oedematous exudate using the procedure as described earlier (39, 40). Immunohistochemistry (IHC) was performed on the lung tissue to detect the presence of SARS-CoV-2 antigen on type-II pneumocytes and alveolar macrophages using the techniques described elsewhere (data not shown here) (39).…”
Section: Methodsmentioning
confidence: 99%